Retinal and Renal Microvasculature in Relation to Central Hemodynamics in 11‐Year‐Old Children Born Preterm or At Term. Issue 15 (4th August 2020) - Wei, Fang‐Fei; Raaijmakers, Anke; Melgarejo, Jesus D.; Cauwenberghs, Nicholas; Thijs, Lutgarde; Zhang, Zhen‐Yu; Yu, Cai‐Guo; Levtchenko, Elena; Struijker‐Boudier, Harry A. J.; Yang, Wen‐Yi; Kuznetsova, Tatiana; Kennedy, Sean; et al.
Abstract : Background: Prematurity disrupts the perinatal maturation of the microvasculature and macrovasculature and confers high risk of vascular dysfunction later in life. No previous studies have investigated the crosstalk between the microvasculature and macrovasculature in childhood. Methods and Results: In a case‐control study, we enrolled 55 children aged 11 years weighing <1000 g at birth and 71 matched controls (October 2014–November 2015). We derived central blood pressure (BP) wave by applanation tonometry and calculated the forward/backward pulse waves by an automated pressure–based wave separation algorithm. We measured the renal resistive index by pulsed wave Doppler and the central retinal arteriolar equivalent by computer‐assisted program software. Compared with controls, patients had higher central systolic BP (101.5 versus 95.2 mm Hg, P <0.001) and backward wave amplitude (15.5 versus 14.2 mm Hg, P =0.029), and smaller central retinal arteriolar equivalent (163.2 versus 175.4 µm, P <0.001). In multivariable analyses, central retinal arteriolar equivalent was smaller with higher values (+1 SD) of central systolic BP (−2.94 µm; 95% CI, −5.18 to −0.70 µm [ P =0.011]) and forward (−2.57 µm; CI, −4.81 to −0.32 µm [ P =0.026]) and backward (−3.20 µm; CI, −5.47 to −0.94 µm [ P =0.006]) wave amplitudes. Greater renal resistive index was associated with higher backward wave amplitude (0.92 mm Hg, P =0.036). Conclusions: In childhood, prematurity compared with term birth is associated with higher central systolic BP and forward/backward wave amplitudes. Higher renal resistive index likely moves reflection points closer to the heart, thereby explaining the inverse association of central retinal arteriolar equivalent with central systolic BP and backward wave amplitude. These observations highlight the crosstalk between the microcirculation and macrocirculation in children. Registration: URL: http://www.clinicaltrials.gov . Unique Identifier: NCT02147457.